(untitled) (Academia Journal of Medicine, 2025)
The effective delivery of dental care can often be hindered by a child’s reluctance to cooperate. It is essential to explore psychological behavior management methods that effectively reduce anxiety during dental visits while fostering a positive attitude towards dental procedures. Despite the availability of numerous behavior management techniques, the chosen approach must also be acceptable to parents. Among these techniques, distraction is one of the most commonly utilized and well-received by parents. It involves diverting children’s attention away from what they may perceive as unpleasant procedures. Recently, virtual reality distraction (VRD) has emerged as an innovative and increasingly recognized method for providing this diversion. The aim of this research is to thoroughly examine the virtual reality distraction technique.